(3GdfUM GdCfaYs - (3CMeO Hf RQhb GdaGSj, RQhb,J (B899 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3jHOC GdehLhO efg HaUd ai MbjbI GdHOYI hNhGUgG hCMcGegG (B: (3CeG MbjbI GdHOYI aTQYkG EMOGK CeQ ai GdOjf jTHg Cf jchf efg hdjS efg s
(3BNQgG (B:s
(3hMOjK HSe Gddg GdPi dGjVQ eY ESeg TF KdGKkG UHGMkG hKdGKkG eSGA QhGg CHh OGhO Yf YKeGf hbGd GdJQePi MSf UMjM s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JUha (B137) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs